Hambatan Generasi Baby Boomers dalam Mengadopsi Dompet Digital di Indonesia - Agusta Ika Prihanti Nugraheni; Neni Pancawati; Nova Perwira Yuda (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Currently, fintech has become an important part of the lifestyle and financial situation in the world because it helps develop new startups and can even improve people's living standards. An example of fintech innovation is electronic money or e-money which consists of two types, namely e-money which is chip based and also server based. Currently, most of the fintech users are the millennial’s generation. Meanwhile, the baby boomer’s generation has challenges in using technology so that it is considered a less potential market. The baby boomer’s generation is considered a conservative generation in adopting new technology or products with new technology. On the other hand, the government and Bank Indonesia are working to encourage non-cash transactions, which are better known as the Gerakan Nasional Non Tunai (GNNT). This study aims to explore the factors that hinder the baby boomer’s generation from adopting digital wallets in Indonesia. The research model is qualitative research. Data collection was carried out by interviews based on Innovation Resistance Theory. The results show form the informan who already used digital wallet and who haven't used stated that the biggest barrier in using digital wallet are risk and usage barrier. Hopefully the results can be used to comprehend more about the obstacles faced by the baby boomer’s generation in utilizing digital wallets, so that companies or marketers who can use them in developing digital wallet marketing strategies and developing their services and also to support GNNT program.